Infant Alveolar Macrophages Are Unable to Effectively Contain Mycobacterium tuberculosis - Goenka, Anu; Prise, Ian E.; Connolly, Emma; Fernandez-Soto, Paulina; Morgan, David; Cavet, Jennifer S.; Grainger, John R.; Nichani, Jaya; Arkwright, Peter D.; Hussell, Tracy (Frontiers in Immunology, 2020)
Infants are more likely to develop lethal disseminated forms of tuberculosis compared with older children and adults. The reasons for this are currently unknown. In this study we test the hypothesis that antimycobacterial function is impaired in infant alveolar macrophages (AMfs) compared with those of adults. We develop a method of obtaining AMfs from healthy infants using rigid bronchoscopy and incubate the AMfs with live virulent Mycobacterium tuberculosis (Mtb). Infant AMfs are less able to restrict Mtb replication compared with adult AMfs, despite having similar phagocytic capacity and immunophenotype. RNA-Seq showed that infant AMfs exhibit lower expression of genes involved in mycobactericidal activity and IFNγ-induction pathways. Infant AMfs also exhibit lower expression of genes encoding mononuclear cell chemokines such as CXCL9. Our data indicates that failure of AMfs to contain Mtb and recruit additional mononuclear cells to the site of infection helps to explain the more fulminant course of tuberculosis in early life.